2009
DOI: 10.2131/jts.34.541
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin induces Yca1p-dependent cell death of yeast Saccharomyces cerevisiae

Abstract: -Tributyltin chloride (TBT), an environmental pollutant, is toxic to a variety of eukaryotic and prokaryotic organisms. Although it has been reported that TBT induces apoptotic cell death in mammalian, the action of TBT on eukaryotic microorganisms has not yet been fully investigated. In this study we examined the mechanism involved in cell death caused by TBT exposure in Saccharomyces cerevisiae. The median lethal concentration of TBT was 10 μM for the parent strain BY4741 and 3 μM for the pdr5 -tions reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
(5 reference statements)
4
12
0
Order By: Relevance
“…Even in the presence or absence of functional Bfr1p, TBT at the low concentration decreased the growth rate but did not induce cell death of S. pombe, while at the high concentration (more than ten micromolar) it induced cell death. These results are in parallel with the concentration-dependent action of TBT in cell cycle and cell death previously observed in S. cerevisiae (Chahomchuen et al, 2009).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Even in the presence or absence of functional Bfr1p, TBT at the low concentration decreased the growth rate but did not induce cell death of S. pombe, while at the high concentration (more than ten micromolar) it induced cell death. These results are in parallel with the concentration-dependent action of TBT in cell cycle and cell death previously observed in S. cerevisiae (Chahomchuen et al, 2009).…”
Section: Resultssupporting
confidence: 88%
“…We have found that TBT induced apoptosis in S. cerevisiae, which was Yca1p-dependent and likely mediated by production of reactive oxygen species (Chahomchuen et al, 2009). Whether a decrease in the cell viability of S. pombe by TBT at high concentrations (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The yeast metacaspase, termed Yeast Caspase1 (YCA1), is required for various stress-induced cell death events, including oxidative, osmotic, toxic, and virus-induced stresses and aging (Madeo et al, 2002;Herker et al, 2004;Ivanovska and Hardwick, 2005;Chahomchuen et al, 2009). YCA1 is also involved in cell cycle regulation (Lee et al, 2008) and clearance of insoluble protein aggregates (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%